Suicide behavior among patient with mental disorder - Catur Budi Rahayu; Siti Nurjanah (UM Purwokerto Press, 2020)
Suicide is an act consciously taken by a person to end his life. The phenomenon of suicide in Indonesia is increasingly worrying. Indonesia, as a country that adheres to a culture of collectivity, also has a high suicide rate. WHO estimates that in 2020 the suicide rate in Indonesia could reach 2.4 percent of 100,000 people if it does not get serious attention from various parties.Suicide is one of the effects of mental disorders that are in the global spotlight today. This study aims to describe suicidal behavior in patients with mental disorders. This is a descriptive study. The research subjects were schizophrenic they were treated in the Installation of Integrated Mental Health Service in Banyumas Hospital. The data were collected using the Self Harm Behavior questionnaire. Result of the study is suicidal behavior are the desire to die, trying with sharp objects, hitting selves, hitting glass and drinking poisonous substance, and jumping from high building.